Mitigation effects of plant carbon black on intestinal morphology, inflammation, antioxidant status, and microbiota in piglets challenged with deoxynivalenol - Wu, Jie; Wang, Hanyang; Liao, Jianling; Ke, Linfu; Lu, Deqiu; Deng, Bo; Xu, Ziwei (Frontiers in Immunology, 2024)
Introduction Plant carbon black (PCB) is a new feed additive for zearalenone adsorption in China. However, information regarding whether PCB can effectively absorb deoxynivalenol (DON) is limited. Methods To explore this research gap, the present study examined the adsorption effectiveness of DON by PCB using a phosphate buffer, artificial gastric juice, and artificial intestinal juice. In a 21-day in vivo trial, 48 male piglets were randomly assigned to four treatment groups: (1) uncontaminated basal diet (CTR), (2) basal diet supplemented with 1 mg/kg PCB(PCB), (3) 2.3 mg/kg DON-contaminated diet (DON), and (4) 2.3 mg/kg DON-contaminated diet supplemented with 0.1% PCB (DON+PCB). Results When DON concentration was 1 µg/mL, the adsorption rate of PCB on DON in phosphate buffer systems (pH 2.0 and 6.0) and the artificial gastric and intestinal juices were 100%, 100%, 71.46%, and 77.20%, respectively. In the in vivo trial, the DON group significantly increased the DON+deepoxy-deoxynivalenol (DOM-1) content in serum as well as the inflammation cytokine proteins (interleukin-6, interleukin-8, and tumor necrosis factor-α) and mRNA expression of interleukin-6 and longchain acyl-CoA synthetase 4 in the jejunum and ileum. It decreased the villus height, goblet cells, mucosal thickness, and mRNA expression of Claudin-1 compared to the CTR group. In addition, DON decreased the Shannon and Simpson indices; reduced the relative abundances of Firmicutes, Lactobacillus, Candidatus_Saccharimonas, and Ruminococcus; and increased the relative abundances of Terrisporobacter and Clostridium_sensu_stricto_1 in the cecal content. Discussion In conclusion, these results suggest that PCB showed high adsorption efficacy on DON in vitro, and exhibit the protective effects against various intestinal toxicity manifestations in DON-challenged piglets.